Historical overview of the captivity of Ṣafiyyah bint Ḥuyay bin Akhṭab An-Nadhariyah (RA) - Suleiman, Hassan (ApaKhabarTV, 2023)
Some people may be doubting their perceptions of Ṣafiyyah bint Ḥuyay bin Akhṭab; may Allāh be pleased with her. In the conflict with Prophet Muḥammad's army, she lost her father, brother, and husband. However, she eventually married Muḥammad SAW, who had directed his forces to wage war against her family and her people. Some historical information can be the answer to this query and dispel the misconceptions of people who disagree with Islamic law regarding Ṣafiyyah's (RA) captivity. So, who is Ṣafiyyah bint Ḥuyay bin Akhṭab in reality?